Rosé All Day Brand Communication Strategy in Facing the Boycott Issue - Bidi Ashri Meidini; Sri Wahyuning Astuti (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
ABSTRACT This research aims to analyse the communication strategies used by the Rosé All Day brand in dealing with the boycott issue, specifically related to the controversy involving one of its founders. This research method uses a descriptive qualitative approach with a literature review to analyse effective communication strategies in managing controversial issues. The research involved collecting and analysing literature related to crisis communication strategies, public relations, and brand management. The results of this study indicate that as a local brand company in the Indonesian cosmetics industry, it faces serious challenges in managing boycott issues. Through the analysis of communication strategies, this research identified several strategies that were effective in managing the boycott issue, including: improving relationships with the public, responding quickly, establishing positive partnerships, and prioritising accurate two-way communication. In addition, this research also analyses Rosé All Day Cosmetics' brand communication strategies on social media, especially Instagram and TikTok. These strategies include the use of creative content, interaction with followers, positive campaigns and collaboration with influencers. The findings of this study provide more understanding of effective communication strategies in dealing with controversial issues for similar companies. The results may also provide valuable insights for public relations practitioners and brand managers in managing reputational crises related to sensitive issues in competitive markets. Keywords: Boycott, Cosmetics Brand, Instagram, Communication, TikTok.